2008
DOI: 10.2754/avb200877010111
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Coccidian Species in the Water Buffalo (Bubalus Bubalis) in the Province of Afyon, Turkey

Abstract: The objective of this study was to identify the coccidian species present in water buffaloes in the vicinity of Afyon. Faecal samples were collected directly from the rectum of a total of 104 water buffaloes, and examined in the laboratory using Sheather's saturated sugar solution. Faecal samples found to contain Eimeria species were mixed with a solution of 2.5% potassium dichromate, left at room temperature in petri dishes until the oocysts sporulated, and then examined in order to identify the species.Eleve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 4 publications
3
9
0
Order By: Relevance
“…and E. bovis were 40% and 14.8%, respectively. Different results were obtained by Nalbantoglou et al (2008) in the Province of Afyon, Turkey, where the prevalence of Eimeria spp. in buffaloes was 3.8%-55.1%, whereas Singh et al (2012) in India (Ludhiana District, Punjab) found prevalence of the infection which amounted to 0.95% and Mamun et al (2011) in Bangladesh (Kurigram district) found 3.39%.…”
Section: Discussionmentioning
confidence: 80%
“…and E. bovis were 40% and 14.8%, respectively. Different results were obtained by Nalbantoglou et al (2008) in the Province of Afyon, Turkey, where the prevalence of Eimeria spp. in buffaloes was 3.8%-55.1%, whereas Singh et al (2012) in India (Ludhiana District, Punjab) found prevalence of the infection which amounted to 0.95% and Mamun et al (2011) in Bangladesh (Kurigram district) found 3.39%.…”
Section: Discussionmentioning
confidence: 80%
“…The findings of the present study are in close agreement with that of Yu et al (2011) who reported 34.94 % positivity for coccidian infections. Further, a high prevalence rate of 75.0 % has been reported in adult buffaloes from Turkey (Nalbantoglu et al 2008) who also mentioned about the presence of novel Isospora spp. oocyst in buffaloes.…”
Section: Discussionmentioning
confidence: 97%
“…E. zuernii, E. bovis, E. subspherica, E. cylindrica, E. illinoisensis, E. brasiliensis, E. canadensis, E. ellipsoidalis, E. auburnensis and E. alabamensis were recorded. Around 17 species of coccidian species had been reported from dairy animals around the world (Nalbantoglu et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Research performed in other countries has revealed prevalence rates of Eimeria spp. varying from 17.9% to 93% in Poland (Pilarczyk et al 2000;Klockiewicz et al 2007;Pilarczyk et al 2009), 33% in Hungary (Farkas et al 2007), 22.6% and 33.3% in Brazil (Almeida et al 2011;Poscoti-Bruhn et al 2011), 35% to 47.1% in China (Yu et al 2011;Dong et al 2012), 50% in Pakistan (Nisar-Khan et al 2013), 22.7% and 68% in Ethiopia (Abebe et al 2008;Dawid et al 2012), 20%, 68% and 75% in Turkey (Arslan and Tuzer 1998;Cicek et al 2007;Nalbantoglu et al 2008), 29%, 50% and 52% in South Africa (Matjila and Penzhorn 2002), and 35% in Tanzania (Chibunda et al 1997). The rate was reported to be 21.3% and 18% to 50% in the Kurdistan and East-Azerbaijan provinces of Iran (Yakhchali and Gholami 2008;Yakhchali and Zarei 2008;Davoudi et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Coccidiosis is commonly a self-limiting disease; most signs of bovine coccidiosis are chronic or subclinical (Nalbantoglu et al 2008). The clinical picture of coccidiosis depends on the innate pathogencity of different Eimeria species.…”
mentioning
confidence: 99%